Comparative external validation of the PRECISE-DAPT and PARIS risk scores in 4424 acute coronary syndrome patients treated with prasugrel or ticagrelor. (15th February 2020) - Bianco, Matteo; D'ascenzo, Fabrizio; Raposeiras Roubin, Sergio; Kinnaird, Tim; Peyracchia, Mattia; Ariza-Solé, Albert; Cerrato, Enrico; Manzano-Fernández, Sergio; Gravinese, Carol; Templin, Christian; Destefanis, Paola; Velicki, Lazar; et al.
Abstract: Background: The PRECISE-DAPT and PARIS risk scores (RSs) were recently developed to help clinicians at individualizing the optimal dual antiplatelet therapy duration (DAPT) after percutaneous coronary intervention (PCI). Nevertheless, external validation of these RSs it has not yet been performed in ACS (acute coronary syndrome) patients treated with prasugrel or ticagrelor in a real- world scenario. Methods: 4424 ACS patients who underwent PCI and survived to hospital discharge, from January 2012 to December 2016 at 12 European centers, were included. PRECISE-DAPT and PARIS bleeding RS, as well as PARIS ischemic RS, were computed, and their performance at predicting major bleeding (MB; BARC type 3 or 5) and ischemic events (MI and stent thrombosis) during follow up was compared. Results: After a median follow-up of 14 (interquartile range 12–20.9) months, 83 (1.88%) patients developed MB and 133 (3.0%) suffered an ischemic episode. PRECISE-DAPT performed better than PARIS bleeding RS (c-statistic = 0.653 vs. 0.593; p = .01 for comparison) in predicting MB. The RSs performance for MB prediction remained consistent in STEMI patients (c-statistic = 0.632 vs 0.575) or in those treated with prasugrel (c-statistic = 0.623 vs 0.586). PARIS ischemic RS exhibited superior discrimination in predicting ischemic complications compared to PRECISE-DAPT (c-statistic = 0.604 vs 0.568 p = .05 for comparison). Conclusion: Our data provide support to the use of PRECISE-DAPT in MB risk stratification for patients receiving DAPT in form of aspirin and prasugrel or ticagrelor whereas the PARIS ischemic RS has potential to complement the risk prediction with respect to ischemic events. Highlights: PRECISE-DAPT performed better than PARIS bleeding RS (c-statistic = 0.650 vs. 0.593; p = .01 for comparison) in predicting MB. The decision curves analysis demonstrated that the use of PRECISE-DAPT is superior to PARIS bleeding RS at a MB risk threshold of ≥2%. PARIS ischemic RS exhibited superior discrimination in predicting ischemic complications compared to PRECISE-DAPT (c-statistic = 0.604 vs 0.568 p = .05 for comparison).